Bio-energy Carriers as Back-up Fuel in Hybrid Solar Power Plants. Issue 1 (July 2020) - Baeyens, Jan; Li, Shuo; Zhang, Huili; Dewil, Raf; Flamant, Gilles; Ansart, Renaud; Deng, Yimin
Abstract: Electricity from concentrated solar power (CSP) plants, gains an increasing interest and importance. To fully match the supply-demand principle, CSP processes include a thermal energy storage and back-up fuel supply. Novel CSP concepts are needed with specific targets of increased efficiency and reliability, and of reduced CAPEX and OPEX. The use of particle suspensions offers significant advantages since applicable in all sub-sections of the complete CSP as heat carrier from the receiver, to the heat storage, and ultimately to the power block. The use of particles in the steam generation (power block) is a common fluidized bed boiler technology. This paper will present the entire particle-based concept, while also discussing the potential to use biomass-based energy carriers as back-up heat supply. Process data and expected effects on the process economy of the system will be discussed.